TIME OPTIMIZATION 3D RESISTIVITY MODELING OF WENNER CONFIGURATION USING FINITE ELEMENT METHOD - Taufik, Arizal
Numerical methods can be used in modelling a complex physical problem. This research uses one of the numerical methods, namely the finite element method. This method is applied to solve the problem of boundary conditions in the potential response of the injected current into a homogeneous model. Other problems in modelling with the three-dimensional domain 3-D are finding solutions and computation time. Optimization method of memory allocation and sparse matrix is as a solution to increase computational efficiency. The resistivity modelling method uses electrodes that act as transmitters and receivers. The results in the form of potential distribution values, measurement of potential difference using the Wenner a configuration obtained a value of 1.6948 volts, Wenner b value is 0.58215 volts, and Wenner g is 1.1127 volts. The application of the memory allocation technique and the sparse matrix yield significant results in computation time. The computation time before application is 150 seconds in modelling one measurement configuration. After being applied, the modelling time was 20 seconds.